South Asian archaeology studies - Possehl, Gregory L. (New Delhi : Oxford & IBH Pub. Co., 1992)
Contributed articles.
Includes bibliographical references.
Keywords: Excavations (Archaeology) -- South Asia; South Asia -- Antiquities